Continuous non-invasive monitoring improves blood pressure stability in upright position: randomized controlled trial - Benes, Jan; Simanova, Alena; Tovarnicka, Tereza; Sevcikova, Silvie; Kletecka, Jakub; Zatloukal, Jan; Pradl, Richard; Chytra, Ivan; Kasal, Eduard (Journal of clinical monitoring and computing, 2015)
Intermittent blood pressure (BP) monitoring is the standard-of-care during low and intermediate risk anaesthesia, yet it could lead to delayed recognition of BP fluctuations. Perioperative hypotension is known to be associated with postoperative complications. Continuous, non-invasive methods for BP monitoring have been developed recently. We have tested a novel non-invasive, continuous monitor (using the volume clamp method) to assist with maintaining BP in safe ranges for patients undergoing surgery in a beach chair position. Forty adult patients undergoing thyroid gland surgery in an upright position were included in this prospective randomised controlled trial. Patients were equally allocated to the group with continuous monitoring of BP using the CNAP® Monitor and to the control group managed using an intermittent oscillometric BP cuff. The absolute and proportional time spent outside the range of ±20% of the target BP along with other hemodynamic and clinical parameters were evaluated. The continuous monitoring decreased the anaesthesia time spent below -20% pressure range [absolute: 12 min (4-20) vs. 27 min (16-34); p=0.001; relative to procedure length: 14% (7-20) vs. 33.5% (17.5-53); p=0.003]. No significant differences were observed in postoperative morbidity or in hospital length of stay. Continuous non-invasive BP monitoring via the CNAP® Monitor allows for better BP management in patients undergoing surgery in a beach chair position. In our randomised trial the time spent in hypotension was significantly shorter using continuous monitoring.
Keywords: Oscillometry; dospělí; Female; monitorování fyziologických funkcí; Adult; oscilometrie; výsledek terapie; ženské pohlaví; Blood Pressure Monitors; Monitoring, Physiologic; lidé; katetrizace; anesteziologie; Treatment Outcome; anestezie; monitory krevního tlaku; krevní tlak; peroperační monitorování; prospektivní studie; Male; Hypotension; Aged; Prospective Studies; Anesthesiology; Blood Pressure Determination; Anesthesia; Patient Positioning; Catheterization; hypotenze; měření krevního tlaku; lidé středního věku; senioři; mužské pohlaví; Monitoring, Intraoperative; Blood Pressure; polohování pacienta; Middle Aged; Humans